2016
DOI: 10.1002/ams2.248
|View full text |Cite
|
Sign up to set email alerts
|

Non‐traumatic bladder rupture showing less than 10 Hounsfield units of ascites

Abstract: Aim: Bladder ruptures are commonly misdiagnosed as gastrointestinal perforations or intestinal ischemia. If a diagnosis is made preoperatively, conservative treatment is a safe and effective option. We evaluated the validity of using the attenuation value of ascites, measured by non-contrast computed tomography (CT), to identify patients with bladder ruptures.Methods: A retrospective search of our hospital database identified 7 patients with confirmed bladder ruptures between 2007 and 2013. We also enrolled 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Notably, our patient had sepsis because of bladder perforation induced by intravesical BCG treatment and the bladder perforation developed into a fluctuant perivesical abscess and bilateral ureteral obstruction. Some reports have revealed the causes of bladder perforation, including TURBT, interstitial cystitis, neurogenic bladder, radiation cystitis, bladder cancer and an indwelling urethral catheter [9][10][11]. Recently, bladder perforation associated with instillation of intravesical mitomycin C (MMC) after TURBT was reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our patient had sepsis because of bladder perforation induced by intravesical BCG treatment and the bladder perforation developed into a fluctuant perivesical abscess and bilateral ureteral obstruction. Some reports have revealed the causes of bladder perforation, including TURBT, interstitial cystitis, neurogenic bladder, radiation cystitis, bladder cancer and an indwelling urethral catheter [9][10][11]. Recently, bladder perforation associated with instillation of intravesical mitomycin C (MMC) after TURBT was reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, the patients were often complained of non-specific symptoms; abdominal pain (83%), following fever (37.5 °C or higher), abdominal distension and urinary retention. It is clinically important to differentiate unexpected NTBR from other acute abdomen by CT findings [ 8 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Perforation of the small intestine is more common and represents similar CT findings. Mizumura et al reported that BR should be considered when the ascites showed less than 10 HU [ 8 ]. CT values of ascites were not specific, but a massive low dense ascites reached to the liver surface can be the key to differentiate BR from small bowel perforation.…”
Section: Clinical Characteristicsmentioning
confidence: 99%